Relationship between domestic fuel price and economic sectors in Malaysia - Jee, Brenda Hui Siang (Universiti Malaysia Sarawak, 2009)
Generally, this study aims to examine the relationship between domestic fuel price and the 10 disaggregated economic sectors in Malaysia. Specifically, we intend to find out the short-run and long-run relationships between these examined variables and to some extent, measure the influence of fuel price on the respective economic sectors. Standard econometric estimating methodologies have been applied in this study. The result from the vector error correction model (VECM) have further indicated that fuel price does Granger cause these economic sectors in the long term and therefore is a relatively exogenous variable in this study. In general, three patterns have been observed for these relations under the generalized variance decomposition analysis (GVDCs).